The examination of the nephroprotective effect of montelukast sodium and N-acetylcysteine ın renal ıschemia with dimercaptosuccinic acid imaging in a placebo-controlled rat model - Aydin,Arif (2020)
Abstract Purpose To determine the nephroprotective effect of NAC and Montelukast Sodium administration against the development of renal damage associated with long warm renal ischemia. Methods Twenty-seven rats were randomly divided into 3 study groups, which received NAC, montelukast and placebo, and 3 rats were included in the sham-treated control group. Medications were given 3 days before the procedure. DMSA renal scintigraphy was performed before and after surgery. The right renal pedicle was occluded for 45 min to induce ischemia and then subjected to reperfusion for 6 h (I/R groups). Results On pathological examination, the mean pathological scores of the montelukast and NAC groups were significantly lower than those of the placebo group. (p <0.05). In biochemical examination, significant differences were found in all parameter levels between the placebo group and the montelukast and NAC groups. (p <0.05) When postoperative DMSA renal scintigraphy measurements and renal function levels were compared, significant differences were found between the montelukast and NAC groups and the placebo and sham groups. Conclusion The administration of NAC and montelukast sodium was seen to have a nephroprotective effect against the development of renal damage associated with warm renal ischemia.